2022
DOI: 10.17816/dd104358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on the reliability of the CT0–4 grading system: a comparison of computed tomography protocols

Abstract: BACKGROUND: The increased frequency of chest computed tomography utilization in the fight against COVID-19 has made usage of low-dose computed tomography necessary to reduce the radiation dose while preserving diagnostic quality. However, in the published literature, there were no data on the effect of body mass index on low-dose computed tomography accuracy in patients with COVID-19. AIM: To assess the effect of patient body mass index on the level of agreement between radiologists interpreting standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…[58], ограничением НДКТ органов грудной клетки в рутинной практике представляется ожирение (индекс массы тела >25) за счёт поглощения рентгеновского излучения жировой тканью. Однако результаты исследований согласованности оценки степени тяжести COVID-19 между экспертами указывают на обратное [59].…”
Section: ограничения низкодозной компьютерной томографииunclassified
“…[58], ограничением НДКТ органов грудной клетки в рутинной практике представляется ожирение (индекс массы тела >25) за счёт поглощения рентгеновского излучения жировой тканью. Однако результаты исследований согласованности оценки степени тяжести COVID-19 между экспертами указывают на обратное [59].…”
Section: ограничения низкодозной компьютерной томографииunclassified
“…According to the registry, obese individuals had a greater prevalence of hypoxemia and radiographic abnormalities on chest X-rays, according to Hendren et al 24 Regarding the CT score in the current study, a score-3 was frequently detected in underweight and overweight patients, and a score-5 was frequently observed in obese patients. Blokhin et al 28 concluded that body mass index does not affect chest standard-dose and low-dose computed tomography interpretation in COVID-19, using the visual semiquantitative CT 0-4 grading system. According to Lu et al 29 at the time of admission and at 5-month intervals, CT scans of obese individuals revealed more severe pneumonia lesions.…”
mentioning
confidence: 99%